Initial Clinical Trial of Robot of Endovascular Treatment with Force Feedback and Cooperating of Catheter and Guidewire - Yuhua Jiang; Keyun Liu; Youxiang Li (Applied Bionics and Biomechanics)
To evaluate the feasibility and safety of the robot of endovascular treatment (RobEnt) in clinical practice, we carried out a cerebral angiography using this robot system. We evaluated the performance of application of the robot system to clinical practice through using this robotic system to perform the digital subtraction angiography for a patient who was suspected of suffering intracranial aneurysm. At the same time, through comparing the postoperative head nuclear magnetic and blood routine with the preoperative examination, we evaluated the safety of application of the robot system to clinical practice. We performed the robot system to complete the bilateral carotid artery and bilateral vertebral arteriography. The results indicate that there was no obvious abnormality in the patient’s cerebral artery. No obvious abnormality was observed in the examination of patients’ check-up, head nuclear magnetism, and blood routine after the digital subtraction angiography. From this clinical trial, it can be observed that the robot system can perform the operation of cerebral angiography. The robot system can basically complete the related observation indexes, and its accuracy, effectiveness, stability, and safety basically meet the requirements of clinical application in neurointerventional surgery.